Cloning and heterologous expression of Plasmodium ovale dihydrofolate reductase-thymidylate synthase gene - Tirakarn, S; Riangrungroj, P; Kongsaeree, P; Imwong, M; Yuthavong, Y; Leartsakulpanich, U (2012)
Plasmodial bifunctional dihydrofolate reductase-thymidylate synthase (DHFR-TS) is a validated antimalarial drug target. In this study, expression of the putative dhfr-ts of Plasmodium ovale rescued the DHFR chemical knockout and a TS null bacterial strain, demonstrating its DHFR and TS catalytic functions. PoDHFR-TS was expressed in Escherichia coli BL21 (DE3) and affinity purified by Methotrexate Sepharose column. Biochemical and enzyme kinetics characterizations indicated that PoDHFR-TS is similar to other plasmodial enzymes, albeit with lower catalytic activity but better tolerance of acidic pH. Importantly, the PoDHFR from Thai isolate EU266602 remains sensitive to the antimalarials pyrimethamine and cycloguanil, in contrast to P. falciparum and P. vivax isolates where resistance to these drugs is widespread. © 2011 Elsevier Ireland Ltd.